Cesarean section in a parturient with giant lung cyst - Divya Gahlot; Kirti N Saxena; Bharti Wadhwa (Wolters Kluwer Medknow Publications, 2020)
Asymptomatic lung cysts in prepregnant state can have its first manifestation during pregnancy due to altered respiratory physiology. They offer special challenge due to difficult diagnosis and definite treatment during pregnancy. We report case of a 26 years old parturient, G2P1L0 at 36 weeks period of gestation who presented as non resolving pneumothorax which was later diagnosed as a giant lung cyst for cesarean section.